Georgia Architectural and Historic Properties Survey of West Railroad Ave. [8-10], Sycamore, Turner County, Ga., 1981 - Barton and Harbin (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of West Railroad Ave. [8-10], Sycamore, Turner County, Ga., 1981. Several one story commercial brick buildings with flat roofs. Fair and poor condition. Date of Construction: c. 1910. Typical turn of the century small town commercial buildings. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of West Railroad Ave. [8-10], Sycamore, Turner County, Ga., 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 5 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 133 MB (139,649,208 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Sycamore (Ga.); Turner County (Ga.)